High-transparency chitin nanocrystal-based coating and application thereof in food paper
By using high-transparent chitin nanocrystalline coatings, the problems of low transparency, poor waterproof performance and non-bacterial resistance of food packaging paper coatings are solved, and the high transparency and multifunctional performance of food paper are improved.
Patent Information
- Application Number
- CN202510336642.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-21
- Publication Date
- 2025-05-09
- Estimated Expiration
- 2045-03-21
AI Technical Summary
The existing food packaging paper coatings have problems such as low transparency, poor waterproofing and non-bacterial resistance.
Highly transparent chitin nanocrystalline-based coating is used, which consists of chitin nanocrystals, polyvinyl alcohol, silver/chitosan composite antibacterial agent, modified nanotitanium dioxide, nanosilicon dioxide, thickener, plasticizer and antioxidant, and is prepared by uniform mixing and hot air drying.
Improves the transparency of food paper while giving it waterproof, antibacterial and oleophobic properties, enhancing the bond strength and thermal stability of the coating to the paper base.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of food packaging, and in particular to a highly transparent chitosan nanocrystal-based coating and application thereof in food paper. Background Art
[0002] Chitin is the second largest natural high molecular weight polysaccharide after cellulose. It is a linear polymer polysaccharide formed by connecting 2-acetylglucosamine through β-1,4 glycosidic bonds. It is widely found in the bones of crustaceans such as shrimps and crabs, and mollusks such as squid and shellfish. With the development of nanotechnology, its application in the food field has attracted much attention. Nanochitin (NCh) is a type of nanoscale chitin material formed by breaking the long chain structure of chitin by physical or chemical methods. NCh not only has the properties of chitin, but also can form a uniform dispersion in aqueous solution. At the same time, it also has the characteristics of nanomaterials, including small size, low density, high surface area, excellent biocompatibility and mechanical properties, renewability, etc. It has been studied and applied in composite materials, medicine and food. In the field of food, NCh has attracted widespread attention in the application of new food active packaging, emulsifier stabilizer, functional factor carrier, quality improver, etc. due to its superior mechanical properties, barrier properties, amphiphilicity and polyhydroxyl functional groups.
[0003] As a degradable material, paper is widely used in the packaging of various foods or the preparation of disposable containers. Since the fibers in the paper have hydrophilic and lipophilic properties, it is difficult for untreated paper to effectively block the water penetration and grease leakage in the food, which is not conducive to the packaging and storage of food. The method of coating the paper by coating to form a coating, isolating the paper and the food, and improving its waterproof and oil-proof is a common treatment method for existing food packaging or food container paper. At present, the commercially available food packaging paper is waxed and coated in order to prevent oil and moisture. Not only is the oil and moisture-proof effect limited, but long-term placement or high temperature will cause the waxing and coating to gradually penetrate into the paper, causing pollution to the food, affecting the nutrition, flavor and hygiene of the food, and the low transparency of the non-antibacterial, making it difficult to observe the food condition. Therefore, it is urgent to develop a coating containing nano-chitin to overcome the shortcomings of low transparency, poor waterproof performance and non-antibacterial in the current food paper. Summary of the invention
[0004] The purpose of the present invention is to provide a highly transparent chitosan nanocrystal-based coating and its application in food paper to solve the following technical problems: Existing waterproof and moisture-proof coatings applied on the surface of food paper have the problems of low transparency, poor waterproof performance and no antibacterial effect.
[0005] The purpose of the present invention can be achieved through the following technical solutions: A highly transparent chitosan nanocrystal-based coating, wherein the highly transparent chitosan nanocrystal-based coating is prepared by the following method: 70-90 parts by weight of chitin nanocrystal suspension, 5-15 parts by weight of polyvinyl alcohol, 5-15 parts by weight of silver / chitosan composite antibacterial agent, 3-15 parts by weight of modified nano titanium dioxide, 1-5 parts by weight of nano silicon dioxide, 2-5 parts by weight of thickener, 2-10 parts by weight of plasticizer and 0.1-2 parts by weight of antioxidant are uniformly mixed to obtain a highly transparent chitin nanocrystal-based coating.
[0006] As a further solution of the present invention: the preparation method of the modified nano titanium dioxide comprises the following steps: Ammonia water and nano titanium dioxide are dispersed in an ethanol aqueous solution, and then an ethanol solution of methacryloxypropyltrimethoxysilane is added, and the modified nano titanium dioxide is obtained after reaction, centrifugation, washing and drying.
[0007] As a further solution of the present invention: the ammonia water is a 25-30wt% ammonia water solution, and the mass ratio of the methacryloxypropyltrimethoxysilane to the nano-titanium dioxide is 1:6-10.
[0008] As a further solution of the present invention: the preparation method of the silver / chitosan composite antibacterial agent comprises the following steps: The carboxymethyl chitosan is dissolved in deionized water, the pH is adjusted to 10, the temperature is raised to 70-80° C., a silver ammonia solution is added, the solution is dialyzed for purification, dried and ground to obtain a silver / chitosan composite antibacterial agent.
[0009] As a further embodiment of the present invention: the carboxymethyl chitosan and the silver ammonia solution [Ag(NH3)2] + The addition ratio is 100mg:0.4-0.5mmol.
[0010] As a further solution of the present invention: the preparation method of the chitosan nanocrystal suspension comprises at least the following steps: The shrimp and crab shells are sequentially subjected to decalcification, deproteinization and bleaching treatments to obtain purified chitosan; The purified chitosan is suspended in dilute hydrochloric acid for hydrolysis, and after centrifugation, washing and dispersion, a chitosan nanocrystal suspension is obtained.
[0011] As a further solution of the present invention: the content of chitosan nanocrystals in the chitosan nanocrystal suspension is 1-2%, the length of the chitosan nanocrystals is 150-600nm, the aspect ratio is 20-120, the concentration of the dilute hydrochloric acid is 3-5mol / L, the hydrolysis temperature is 60-80°C, and the time is 2-6h.
[0012] As a further embodiment of the present invention: the thickener includes one or a mixture of xanthan gum, sodium alginate or hydroxyethyl cellulose, the plasticizer includes one or a mixture of glycerol, sorbitol or polyethylene glycol, and the antioxidant includes one or a mixture of tea polyphenols, vitamin E or synthetic antioxidants.
[0013] An application of the highly transparent chitosan nanocrystal-based coating as described in any one of the above in food paper, wherein the highly transparent chitosan nanocrystal-based coating can be coated on translucent paper and applied to food paper after drying, curing and calendering.
[0014] As a further solution of the present invention: the coating thickness is 3-20 μm, the coating method is one of blade coating, roller coating or spray coating, and the drying temperature is 50-80° C. Beneficial effects of the present invention: The present invention adopts chitosan nanocrystal as base material, adds polyvinyl alcohol, silver / chitosan composite antibacterial agent, modified nano titanium dioxide, nano silicon dioxide, thickener, plasticizer and antioxidant to prepare coating, and applies it on translucent food paper, thereby improving the transparency of translucent paper and making the translucent paper obtain waterproof, antibacterial and oleophobic properties. Among them, chitosan nanocrystal dispersion can form a film on the surface of base paper, block grease penetration, and improve oil-proof performance, polyvinyl alcohol is used as a binder to improve the bonding strength between the coating and the paper base, the silver / chitosan composite antibacterial agent has both antibacterial effect and can produce synergistic effect with chitosan nanocrystal and polyvinyl alcohol, improve the tensile strength of food paper, and make the coating not easy to fall off, nano silicon dioxide is used as an optical enhancer to ensure the transparency of the coating, the modified nano titanium dioxide is used as a hydrophobic agent to improve the hydrophobic property of the coating, and can produce synergistic effect with nano silicon dioxide to improve transparency, the thickener improves the uniformity of coating coating, the plasticizer improves the flexibility of the coating, and the antioxidant improves the service life of the coating. The highly transparent chitosan nanocrystal-based coating prepared in the present invention can be used for processing functional papers such as transparent packaging paper, antibacterial paper and oil-proof paper, and has broad application scenarios in the fields of food, medicine and high-end printing.
[0015] The invention adopts natural shrimp shells and crab shells as raw materials to prepare chitosan nanocrystals. Such biomass raw materials are rich in sources and have the advantages of being renewable and degradable, which not only reduces environmental pollution, but also has important significance for the high-value utilization of waste materials such as abundant crab shells. Calcium carbonate, protein and pigment in shrimp and crab shells are removed in sequence by dilute acid, dilute alkali and bleaching agent, and then unnecessary parts in chitosan fibers are removed by acid hydrolysis process to form rod-shaped or needle-shaped nanocrystals with high crystallinity, and the length and aspect ratio of the nanocrystals are controlled so that the surface of the obtained chitosan nanocrystals is rich in hydroxyl groups, acetylamino groups and a small amount of amino groups. The presence of amino groups can make the surface of chitosan positively charged, thereby improving the bonding strength of the coating and the paper base. The invention selects polyvinyl alcohol as a binder, and the chitosan nanocrystals and polyvinyl alcohol are mixed in water to generate hydrogen bond interactions, and through hot air drying and heat treatment, more physical crosslinking points are made between the chitosan nanocrystals and the polyvinyl alcohol, thereby improving the thermal stability, water resistance and tensile strength of the coating.
[0016] The present invention prepares a silver / chitosan antibacterial composite antibacterial agent, wherein nanosilver is uniformly loaded in a chitosan network structure, the nanosilver has high purity and good crystal structure, small particle size and uniform size, and avoids agglomeration of nanosilver, which affects antibacterial property and coating transparency, and has great advantages in antibacterial property, safety, durability, etc., compared with a single nanosilver or chitosan antibacterial agent. The amino group of chitosan in the composite antibacterial agent is combined with the hydroxyl group of polyvinyl alcohol through hydrogen bonding or ion dipole action, further strengthening the flexibility and tear resistance of the coating, and improving the folding resistance of food paper. Chitosan has cationic properties, and chitin nanocrystals are positively charged at the same time, and agglomeration is reduced by electrostatic repulsion, while polyvinyl alcohol acts as a "bridge" to promote uniform dispersion of the two, forming a uniform and stable composite matrix, thereby improving the mechanical properties of the coating, and the cations and paper fibers (anions) produce electrostatic adsorption, further improving the bonding strength between the coating and the paper base. The present invention uses methacryloxypropyltrimethoxysilane as a hydrophobic modifier for nano-titanium dioxide. Methacryloxypropyltrimethoxysilane has a relatively long hydrophobic chain and moderate reactivity, and is easy to react with the hydroxyl groups on the surface of nano-titanium dioxide to form a stable covalent bond without the risk of perfluorinated compounds. The present invention selects nano-silicon dioxide as an optical enhancer. Nano-silicon dioxide and nano-titanium dioxide produce a synergistic effect, further improving the transparency of the coating, and the nano-size of the material and the chitin nanocrystals synergistically enhance the mechanical interlocking effect, thereby improving the mechanical properties of the coating. DETAILED DESCRIPTION
[0017] The following will be described clearly and completely in conjunction with the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0018] Example 1 The preparation method of modified nano titanium dioxide comprises the following steps: 20 ml of anhydrous ethanol and 20 ml of water were mixed to obtain an ethanol aqueous solution, the pH was adjusted to 9 with 25 wt % ammonia water, 4 g of nano titanium dioxide was added, and ultrasonic dispersion was performed for 20 min. Then 0.5 g of methacryloxypropyltrimethoxysilane was dissolved in 10 ml of anhydrous ethanol, and added to the above ethanol aqueous solution, and magnetic stirring was performed for 2 h. After the reaction was completed, the reaction solution was evenly divided into centrifuge tubes, and centrifuged at 8000 r / min for 20 min. The lower precipitate was washed with anhydrous ethanol and then dried to obtain modified nano titanium dioxide.
[0019] Example 2 The preparation method of modified nano titanium dioxide comprises the following steps: 20 ml of anhydrous ethanol and 20 ml of water were mixed to obtain an ethanol aqueous solution, the pH was adjusted to 9 with 25 wt % ammonia water, 4 g of nano titanium dioxide was added, and ultrasonic dispersion was performed for 20 min. Then 0.75 g of methacryloxypropyltrimethoxysilane was dissolved in 10 ml of anhydrous ethanol, and added to the above ethanol aqueous solution, and magnetic stirring was performed for 2 h. After the reaction was completed, the reaction solution was evenly divided into centrifuge tubes, and centrifuged at 8000 r / min for 20 min. The lower precipitate was washed with anhydrous ethanol and then dried to obtain modified nano titanium dioxide.
[0020] Example 3 The preparation method of the silver / chitosan composite antibacterial agent comprises the following steps: Weigh 0.136 g of silver nitrate and dissolve it in 10 mL of deionized water. Add 1 mol / L sodium hydroxide solution dropwise and stir continuously until the precipitation no longer increases. Then add 2 wt % ammonia solution dropwise until the precipitation is completely dissolved. Filter with a 0.45 μm filter membrane to obtain a silver ammonia solution. Take 0.2g of carboxymethyl chitosan and dissolve it in 100mL of deionized water, and adjust the pH of the solution to 10 with 1mol / L sodium hydroxide solution, place it in a microwave synthesis reactor (power 600W), raise the system temperature to 70°C, and then quickly inject the above-mentioned silver ammonia solution, start stirring to mix evenly, react for 40min, take it out and cool it to room temperature, then put it into a dialysis bag for dialyzed purification for 3d, and freeze-dry it for 48h to obtain a silver / chitosan antibacterial agent.
[0021] Example 4 The preparation method of chitosan nanocrystal suspension comprises the following steps: The shrimp and crab shells are treated with dilute hydrochloric acid to remove inorganic matter, then with dilute alkali to remove protein, and then with hydrogen peroxide bleaching to increase purity, and decalcification, deproteinization and bleaching are completed in sequence to obtain purified chitin; The purified chitosan was suspended in 4 mol / L dilute hydrochloric acid, hydrolyzed at 70°C for 4 h, and centrifuged to obtain chitosan nanocrystals. The chitosan nanocrystals were then washed repeatedly with deionized water until the pH was close to neutral, and dispersed in deionized water to obtain a chitosan nanocrystal suspension with a solid content of 2%.
[0022] Example 5 The preparation method of highly transparent chitosan nanocrystal-based coating comprises the following steps: 80 parts by mass of the chitosan nanocrystal suspension prepared in Example 4, 10 parts by mass of polyvinyl alcohol, 10 parts by mass of the silver / chitosan composite antibacterial agent prepared in Example 3, 6 parts by mass of the modified nano-titanium dioxide prepared in Example 1, 2 parts by mass of nano-silicon dioxide, 4 parts by mass of thickener sodium alginate, 5 parts by mass of plasticizer polyethylene glycol and 0.5 parts by mass of antioxidant tea polyphenols were added into a high-speed stirrer and mixed evenly to obtain a highly transparent chitosan nanocrystal-based coating.
[0023] Example 6 The preparation method of highly transparent chitosan nanocrystal-based coating comprises the following steps: 80 parts by mass of the chitosan nanocrystal suspension prepared in Example 4, 10 parts by mass of polyvinyl alcohol, 10 parts by mass of the silver / chitosan composite antibacterial agent prepared in Example 3, 6 parts by mass of the modified nano-titanium dioxide prepared in Example 2, 2 parts by mass of nano-silicon dioxide, 4 parts by mass of thickener sodium alginate, 5 parts by mass of plasticizer polyethylene glycol and 0.5 parts by mass of antioxidant tea polyphenols were added into a high-speed stirrer and mixed evenly to obtain a highly transparent chitosan nanocrystal-based coating.
[0024] Example 7 The preparation method of highly transparent chitosan nanocrystal-based coating comprises the following steps: 80 parts by mass of the chitosan nanocrystal suspension prepared in Example 4, 12 parts by mass of polyvinyl alcohol, 8 parts by mass of the silver / chitosan composite antibacterial agent prepared in Example 3, 5 parts by mass of the modified nano-titanium dioxide prepared in Example 1, 1.5 parts by mass of nano-silicon dioxide, 4 parts by mass of thickener sodium alginate, 5 parts by mass of plasticizer polyethylene glycol and 0.5 parts by mass of antioxidant tea polyphenols were added into a high-speed stirrer and mixed evenly to obtain a highly transparent chitosan nanocrystal-based coating.
[0025] Example 8 The preparation method of highly transparent chitosan nanocrystal-based coating comprises the following steps: 80 parts by mass of the chitosan nanocrystal suspension prepared in Example 4, 12 parts by mass of polyvinyl alcohol, 8 parts by mass of the silver / chitosan composite antibacterial agent prepared in Example 3, 5 parts by mass of the modified nano-titanium dioxide prepared in Example 2, 1.5 parts by mass of nano-silicon dioxide, 4 parts by mass of thickener sodium alginate, 5 parts by mass of plasticizer polyethylene glycol and 0.5 parts by mass of antioxidant tea polyphenols were added into a high-speed stirrer and mixed evenly to obtain a highly transparent chitosan nanocrystal-based coating.
[0026] Comparative Example 1 Compared with Example 5, in Comparative Example 1, the modified nano titanium dioxide prepared in Example 1 added in Example 5 is replaced by the unmodified nano titanium dioxide in Example 1, and the other components and preparation method are completely the same as those in Example 5.
[0027] Comparative Example 2 Compared with Example 5, in Comparative Example 2, no nano-silicon dioxide is added, and the remaining components and preparation method are completely consistent with those of Example 5.
[0028] Comparative Example 3 Compared with Example 5, the content of polyvinyl alcohol added in Comparative Example 3 is reduced from 10 parts by mass to 4 parts by mass, and the other components and preparation method are completely consistent with those in Example 5.
[0029] Comparative Example 4 Compared with Example 5, in Comparative Example 3, the silver / chitosan composite antibacterial agent prepared in Example 3 added in Example 4 is replaced by nano silver particles, and the other components and preparation method are completely consistent with those in Example 5.
[0030] Comparative Example 5 Compared with Example 5, in Comparative Example 5, the modified nano titanium dioxide prepared in Example 1 and the silver / chitosan composite antibacterial agent prepared in Example 3 are not added, and the remaining components and preparation methods are completely consistent with those in Example 5.
[0031] Performance Testing Preparation of food paper coated with highly transparent chitosan nanocrystal-based coating: The highly transparent chitosan nanocrystal-based coating obtained in Examples 5-8 and Comparative Examples 1-5 was roller-coated on both sides of the food translucent paper, and hot air dried at 50-80° C.; The dried food paper is calendered by a calender to form a highly transparent chitosan nanocrystal-based coating with a thickness of 5 μm, thereby obtaining food paper coated with a highly transparent chitosan nanocrystal-based coating.
[0032] Tensile strength: The tensile strength of the food paper of the coating material high transparent chitin nanocrystal-based coating obtained in Examples 4-8 and Comparative Examples 1-5 was tested according to TAPPI standard (T494om-96), and expressed in the form of tensile index; the test results are shown in Table 1; Folding resistance: The food paper coated with the highly transparent chitin nanocrystal-based coating obtained in Examples 4-8 and Comparative Examples 1-5 was cut into 200 mm × 500 mm strips, and was repeatedly folded in half at an extension of 250 mm until the coating was broken, and the number of folds was recorded; the test results are shown in Table 1; Transparency: The light transmittance (T%) of the food paper of the coating material high transparent chitin nanocrystal-based coating obtained in Examples 4-8 and Comparative Examples 1-5 was tested by using an ultraviolet-visible spectrophotometer (UV-240, Shimadzu, Japan), and the measured wavelength range was 200-800nm; the test results are shown in Table 1; Hydrophobicity: According to GB / T 30693-2014 standard, the water contact angle of the food paper coated with the highly transparent chitin nanocrystal-based coating obtained in Examples 4-8 and Comparative Examples 1-5 was tested; the test results are shown in Table 1; Antibacterial performance test: Weigh 0.1g of food paper coated with highly transparent chitosan nanocrystal-based coating and cut it into small pieces. Dilute the bacterial solution with physiological saline to 10 5 cfu / mL, add paper to the test tube and place it in a constant temperature shaker (set the temperature to 37°C and shake for 2 hours). After the shaking is completed, dilute the shaken bacterial solution again to 10 3 Then, the plates were coated. The plates were placed in an incubator with the temperature and humidity controlled at 72% RH. After 24 hours of incubation, the plates were observed. The bacteria used were E. coli and S. aureus. The test results are shown in Table 1. Table 1: Statistical table of performance test data of food paper coated with coating in Examples 5-8 and Comparative Examples 1-5
[0033] As can be seen from Table 1, the highly transparent chitin nanocrystal-based coating material prepared in the present application is coated on the surface of translucent food paper, giving the food paper excellent hydrophobicity, mechanical properties, transparency and antibacterial properties. In Comparative Example 1, the modified nano titanium dioxide is replaced with unmodified nano titanium dioxide, and the hydrophobicity of the obtained coating is greatly reduced. In Comparative Example 2, nano silicon dioxide is not added, and the transparency of the obtained coating is reduced, and the tensile strength is also reduced. In Comparative Example 3, polyvinyl alcohol is not added, and the tensile strength of the obtained coating is reduced, and the coating is easy to fall off. In Comparative Example 4, the silver / chitosan composite antibacterial agent is replaced with nano silver particles, and the tensile strength, bonding strength, antibacterial property and transparency of the obtained coating are all reduced. In Comparative Example 5, modified nano titanium dioxide and silver / chitosan composite antibacterial agent are not added, and the performance of the obtained coating is poor in all aspects.
[0034] The above is a detailed description of an embodiment of the present invention, but the content is only a preferred embodiment of the present invention and cannot be considered to limit the scope of implementation of the present invention. All equivalent changes and improvements made within the scope of the present invention should still fall within the scope of the patent coverage of the present invention.
Claims
1. A highly transparent chitin nanocrystal-based coating, characterized in that: The highly transparent chitosan nanocrystal-based coating is prepared by the following method: 70-90 parts by weight of chitin nanocrystal suspension, 5-15 parts by weight of polyvinyl alcohol, 5-15 parts by weight of silver / chitosan composite antibacterial agent, 3-15 parts by weight of modified nano titanium dioxide, 1-5 parts by weight of nano silicon dioxide, 2-5 parts by weight of thickener, 2-10 parts by weight of plasticizer and 0.1-2 parts by weight of antioxidant are uniformly mixed to obtain a highly transparent chitin nanocrystal-based coating.
2. A highly transparent chitosan nanocrystal-based coating according to claim 1, characterized in that: The preparation method of the modified nano titanium dioxide comprises the following steps: Ammonia water and nano titanium dioxide are dispersed in an ethanol aqueous solution, and then an ethanol solution of methacryloxypropyltrimethoxysilane is added, and the modified nano titanium dioxide is obtained after reaction, centrifugation, washing and drying.
3. A highly transparent chitosan nanocrystal-based coating according to claim 2, characterized in that: The ammonia water is a 25-30wt% ammonia water solution, and the mass ratio of the methacryloxypropyltrimethoxysilane to the nano titanium dioxide is 1:6-10.
4. A highly transparent chitosan nanocrystal-based coating according to claim 1, characterized in that: The preparation method of the silver / chitosan composite antibacterial agent comprises the following steps: The carboxymethyl chitosan is dissolved in deionized water, the pH is adjusted to 10, the temperature is raised to 70-80° C., a silver ammonia solution is added, the solution is dialyzed for purification, dried and ground to obtain a silver / chitosan composite antibacterial agent.
5. A highly transparent chitosan nanocrystal-based coating according to claim 4, characterized in that: [Ag(NH3)2] in the carboxymethyl chitosan and the silver ammonia solution + The addition ratio is 100mg:0.4-0.5mmol.
6. A highly transparent chitosan nanocrystal-based coating according to claim 1, characterized in that: The preparation method of the chitosan nanocrystal suspension comprises at least the following steps: The shrimp and crab shells are sequentially subjected to decalcification, deproteinization and bleaching treatments to obtain purified chitosan; The purified chitosan is suspended in dilute hydrochloric acid for hydrolysis, and after centrifugation, washing and dispersion, a chitosan nanocrystal suspension is obtained.
7. A highly transparent chitosan nanocrystal-based coating according to claim 6, characterized in that: The content of chitosan nanocrystals in the chitosan nanocrystal suspension is 1-2%, the length of the chitosan nanocrystals is 150-600nm, the aspect ratio is 20-120, the concentration of the dilute hydrochloric acid is 3-5mol / L, the hydrolysis temperature is 60-80°C, and the time is 2-6h.
8. The highly transparent chitosan nanocrystal-based coating according to claim 1, characterized in that: The thickener includes one or a mixture of xanthan gum, sodium alginate or hydroxyethyl cellulose, the plasticizer includes one or a mixture of glycerol, sorbitol or polyethylene glycol, and the antioxidant includes one or a mixture of tea polyphenols, vitamin E or synthetic antioxidants.
9. Use of the highly transparent chitosan nanocrystal-based coating according to any one of claims 1 to 8 in food paper, characterized in that: The highly transparent chitosan nanocrystal-based coating can be coated on translucent paper and applied to food paper after being dried, cured and calendered.
10. The use of a highly transparent chitosan nanocrystal-based coating in food paper according to claim 9, characterized in that: The coating thickness is 3-20 μm, the coating method is one of blade coating, roller coating or spray coating, and the drying temperature is 50-80° C.
Citation Information
Patent Citations
High-transparency double-component polyurethane transparent matt top coat top coat and method for preparing same
CN101333410A
Preparation method of nano chitin / polyvinyl alcohol composite film, nano chitin / polyvinyl alcohol composite film prepared by means of preparation method and application of nano chitin / polyvinyl alcohol composite film
CN109134897A
Flashover voltage resistant nano composite coating and preparation method thereof
CN116463055A
Antiviral and antimicrobial barrier coatings
US20240263021A1